2017
DOI: 10.1016/j.conctc.2017.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with willingness to participate in a vaccine clinical trial among elderly Hispanic patients

Abstract: A population specific understanding of barriers and facilitators to participation in clinical trials could improve recruitment of elderly and minority populations. We investigated how prior exposure to clinical trials and incentives were associated with likelihood of participation in a vaccine clinical trial through a questionnaire administered to 200 elderly patients in an academic general internal medicine clinic. Wilcoxon signed rank sum test compared likelihood of participation with and without monetary in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 17 publications
(23 reference statements)
0
15
1
Order By: Relevance
“…By providing financial compensation up to US$ 350, the percentage of WTP increased by 47.2% compared to no compensation (62.3% vs. 15.1%). The increased rate in our study is higher compared to another study that found a 12.2% absolute increase in those reporting that they would not participate after mentioning financial incentive [ 49 ]. This difference between studies could be influenced by the amount of the money offered in the study.…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…By providing financial compensation up to US$ 350, the percentage of WTP increased by 47.2% compared to no compensation (62.3% vs. 15.1%). The increased rate in our study is higher compared to another study that found a 12.2% absolute increase in those reporting that they would not participate after mentioning financial incentive [ 49 ]. This difference between studies could be influenced by the amount of the money offered in the study.…”
Section: Discussioncontrasting
confidence: 88%
“…Previously, studies clearly indicated that good knowledge [ 21 ] and good perception of disease risk [ 46 ] were predictors for a high WTP. Previous studies have also found that community members who have good knowledge regarding a medical study [ 47 ], good perception and high awareness concerning medical research [ 48 ], and prior participation in clinical trials [ 49 ] are more likely to have a positive response to WTP. In contrast, the lack of knowledge and awareness about a medical study is a significant barrier to participating [ 48 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies conducted in high-income countries and in low-income countries on the willingness to participate in clinical trials have reported varied results. In the United Kingdom and United States, poor recruitment rates have been reported and attributed to non-approachable clinicians, fear and mistrust of researchers, patient attitudes, stringent eligibility criteria and lack of knowledge about clinical research [ 6 8 ]. Studies in sub-Saharan Africa showed that participants tend to exhibit a moderate willingness to participate in HIV vaccine trials.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, compensation has a positive impact on individuals' willingness to enroll in a study (Bentley & Thacker 2004), but the reverse may also be true. Rikin, Shea, LaRussa, and Stockwell (2017) noted that incentives for a hypothetical vaccine trial decreased the willingness of the elderly Hispanic study population to be recruited to participate.…”
Section: Recent Research Publications Present Research Focused On Parmentioning
confidence: 99%